Hereditary Hemorrhagic Telangiectasia Presenting as High Output Cardiac Failure during Pregnancy - Tareq Goussous; Alex Haynes; Katherine Najarian; Marcos Daccarett; Shukri David (Cardiology Research and Practice)
High-output cardiac failure secondary to hepatic involvement is a rare complication of hereditary hemorrhagic telangiectasia (HHT). Here we report a 43-year-old woman who presented at 29 weeks gestation of her second pregnancy with complications of right-sided heart failure and preterm labor. After delivery via cesarean section, the patient was found to have intrahepatic arteriovenous malformations through non-invasive imaging. Subsequently, a family history of vascular malformations and epistaxis was elucidated and a diagnosis of HHT was made. This case is presented, along with a review of the literature and discussion of hepatic involvement in HHT with particular focus on the pregnant patient.